Criminal Act of Child Neglect in the Household - Marlissa, Indah Glodia; Adam, Sherly; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Children are one of the groups who often become victims of discrimination, violence and exploitation. As a legal state based on Pancasila as the ideology and foundation of a state that upholds the values of social justice, Pancasila has the aim of achieving balance, or harmony and being able to embrace society.Purposes of the Research: The purpose of this paper is to analyze and discuss the regulation of the crime of child neglect in the household scope in laws and regulations and to analyze and discuss the form of the crime of child neglect in the household scope.Methods of the Research: The type of research used is normative legal research. The problem approach used is the legislative approach and the conceptual approach. The sources of legal materials are primary legal materials and secondary legal materials. The procedure for collecting legal materials through literature studies. Qualitative processing and analysis of legal materials.Findings of the Research: The results of the study show that the regulation of the crime of child neglect in laws and regulations is regulated in the Criminal Code (old), the Child Protection Law, the Domestic Violence Law and Law Number 1 of 2023 concerning the Criminal Code (New). Child neglect is more explicitly regulated in the Child Protection Law. This is based on Article 9 paragraph (1) of the Domestic Violence Law where the provisions indicate that the regulation of the crime of neglect is not limited to children, but rather to a wider scope. Therefore, when the Domestic Violence Law is compared with the Child Protection Law, it is clear that the Child Protection Law specifically regulates child neglect. The results of further research show that child neglect is a form of domestic violence and is included in the category of criminal acts or acts prohibited by criminal law and perpetrators of domestic neglect can be subject to sanctions. The forms of child neglect in the household are physical neglect, educational neglect, emotional neglect and medical neglect.